ANTIBACTERIAL ACTIVITY OF HONEY AGAINST ESBL PRODUCING KLEBSIELLA PNEUMONIAE FROM BURN WOUND INFECTIONS - J., Shah Pratibha; T., Williamson Manita (International Journal of Current Pharmaceutical Research, 2015)
Objective: The present study compares the effect of Manuka and Jambhul honey on ten clinical isolates of Klebsiella pneumoniae producing Extended Spectrum Beta Lactamases (ESBLs) from burn wound infections. Methods: The isolated organisms were identified and screened for ESBL production, which was further confirmed by Confirmatory Phenotypic Disc diffusion test and E-test. The antibacterial activity of Manuka and Jambhul honey was analysed using Agar cup method for varying concentrations of 25%, 50%, 75% and 100%. The Minimum inhibitory concentration (MIC) of Manuka and Jambhul honey against the isolates was determined using Agar dilution method. Results: MIC was found to be in the range of 30%-40% (v/v) for both honey. The average MIC of Manuka for all the 10 isolates was estimated to be 34% whereas that of Jambhul, was 36.5% and this difference was found to be statistically insignificant (P>0.05 t test). Total phenolic content (TPC) in Manuka and Jambhul honey was estimated using Folin's Ciocalteau method and was found to be 1.22 mg TA/gm in Manuka honey and 1.18 mg TA/gm in Jambhul honey. Conclusion: Thus, the study showed that honey may be an effective antimicrobial agent against ESBL producing Klebsiella pneumoniae isolated from burn wound infections. It also proved that antimicrobial activity of Indian Jambhul honey is comparable to New Zealand's Manuka honey.